Addenda on Mussel vs. Muscle - Ralph W. Dexter (Hello World!, 1967)
In issue No. 4 of STERKIANA (May, 1961) I dicussed in considerable detail the use of the spellings of 'mussel' and 'muscle' in reference to bivalve mollusks. Most of the controvery has reveolved about the 'mussel shoals' (officially the Muscle Shoals) of the Tennsesse River. However, the confusion has been world-wide and apparently the varitation of spelling has come about for different reasons. In general, use of the spelling 'muscle' is more recent and preferred. Since publication of my report, a number of other instances of the use of this term have come to my attention which are sufficiently interesting to place on my record.